Conservation of intramembrane proteolytic activity and substrate specificity in prokaryotic and eukaryotic Rhomboids. - Urban, S.; Schlieper, D.; Freeman, M. (Current Biology, 2002)
Rhomboid is an intramembrane serine protease responsible for the proteolytic activation of Drosophila epidermal growth factor receptor (EGFR) ligands. Although nothing is known about the function of the approximately 100 currently known rhomboid genes conserved throughout evolution, a recent analysis suggests that a Rhomboid from the pathogenic bacterium Providencia stuartii is involved in the production of a quorum-sensing factor. This suggests that an intercellular signaling mechanism may have been conserved between prokaryotes and metazoans. However, the function of prokaryotic Rhomboids is unknown. We have examined the ability of eight prokaryotic Rhomboids to cleave the three Drosophila EGFR ligands. Despite their striking sequence divergence, Rhomboids from one Gram-positive and four Gram-negative species, including Providencia, specifically cleaved Drosophila substrates, but not similar proteins such as Transforming Growth Factor alpha (TGFalpha) and Delta. Although the sequence similarity between these divergent Rhomboids is very limited, all contain the putative serine catalytic triad residues, and their specific mutation abolished protease activity. Therefore, despite low overall homology, the Rhomboids are a family of ancient, functionally conserved intramembrane serine proteases, some of which also have conserved substrate specificity. Moreover, a function for Rhomboids in activating intercellular signaling appears to have evolved early.